1996
DOI: 10.1128/jb.178.12.3550-3556.1996
|View full text |Cite
|
Sign up to set email alerts
|

In vivo stability of the Umu mutagenesis proteins: a major role for RecA

Abstract: The Escherichia coli Umu proteins play critical roles in damage-inducible SOS mutagenesis. To avoid any gratuitous mutagenesis, the activity of the Umu proteins is normally kept to a minimum by tight transcriptional and posttranslational regulation. We have, however, previously observed that compared with an isogenic recA ؉ strain, the steady-state levels of the Umu proteins are elevated in a recA730 background (R. Woodgate and D. G. Ennis, Mol. Gen. Genet. 229:10-16, 1991). We have investigated this phenomeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 44 publications
2
38
0
Order By: Relevance
“…When umuDC-dependent TLS was subsequently reconstituted by using purified proteins, the test of biological relevancy was again satisfied when it was found that TLS by Pol V had strict requirement for RecA (6,7,89). It has been suggested that interactions of the UmuDЈ 2 C complex with the end of RecAssDNA filaments position Pol V for its role in the TLS responsible for SOS mutagenesis (90)(91)(92)(93); this positioning seems most likely to involve a direct interaction between UmuDЈ and RecA (90,92,94). It thus appears that this interaction between RecA positioned at a site of DNA damage and UmuDЈ, a component of Pol V, may represent an example of how one polymerase is selectively directed to a particular class of primer termini despite the simultaneous presence of several other DNA polymerases.…”
Section: Translesion Synthesis By Dna Pol V Also Requires Reca and Ssbmentioning
confidence: 99%
“…When umuDC-dependent TLS was subsequently reconstituted by using purified proteins, the test of biological relevancy was again satisfied when it was found that TLS by Pol V had strict requirement for RecA (6,7,89). It has been suggested that interactions of the UmuDЈ 2 C complex with the end of RecAssDNA filaments position Pol V for its role in the TLS responsible for SOS mutagenesis (90)(91)(92)(93); this positioning seems most likely to involve a direct interaction between UmuDЈ and RecA (90,92,94). It thus appears that this interaction between RecA positioned at a site of DNA damage and UmuDЈ, a component of Pol V, may represent an example of how one polymerase is selectively directed to a particular class of primer termini despite the simultaneous presence of several other DNA polymerases.…”
Section: Translesion Synthesis By Dna Pol V Also Requires Reca and Ssbmentioning
confidence: 99%
“…The recombination removed the Kan r cassette and produced the ⌬dinB strain (YG6162). To construct YG6168, ⌬(umuDC)596::ermGT was transferred to AB1157 using the DE2302 and EC8 strains as described previously for two-step P1 transduction (19,78). YG6171 (a dinB umuDC double mutant) was constructed by introduction of ⌬dinB::Kan r into YG6168, followed by removal of the Kan r cassette as described above.…”
Section: Methodsmentioning
confidence: 99%
“…1A). To demonstrate that the ⌬dinB61::ble substitution allele is nonpolar, reverse (6), and RW532 do not normally contain FЈ episomes, but for the M13 experiments described herein, they carry the FЈIQ from DH5␣FЈIQ.…”
Section: Methodsmentioning
confidence: 99%